2021
DOI: 10.2147/jhc.s327339
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental Validation of Novel Glypican 3 Exosomes for the Detection of Hepatocellular Carcinoma in Liver Cirrhosis

Abstract: Background and Aims: Hepatocellular carcinoma (HCC) developing in the context of preexisting cirrhosis is characterized by impaired autophagy that results in increased exosome release. This study was conducted to determine whether circulating exosomes expressing glypican 3 (GPC3) could be utilized as a biomarker for HCC detection and treatment response in patients with cirrhosis. Methods: Immunohistochemistry was performed to assess p62 and GPC3 expression in the lesion and adjacent tissue from cirrhosis with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…Our laboratory recently showed that exosomal GPC3 is closely related to the impairment of autophagy by using ELISA analysis of HCC samples. 33 However, using the immuno-magnetic affinity assay, we show that GPC3 is restricted to the exosomal EV fraction both in the hepatoma cell lines and in the HCC samples. This suggests that GPC3 plays a major role in the biogenesis of multivesicular bodies and exosome release.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our laboratory recently showed that exosomal GPC3 is closely related to the impairment of autophagy by using ELISA analysis of HCC samples. 33 However, using the immuno-magnetic affinity assay, we show that GPC3 is restricted to the exosomal EV fraction both in the hepatoma cell lines and in the HCC samples. This suggests that GPC3 plays a major role in the biogenesis of multivesicular bodies and exosome release.…”
Section: Discussionmentioning
confidence: 79%
“…We previously showed that GPC3 expressing exosomes can be detected in the serum of patients with HCC cirrhosis. 33 Solid malignancies, including HCC, excrete both exosomes and microvesicles but which type of particle is selected by HCC for releasing GPC3 is not elucidated. Using the immuno-magnetic affinity assay, we examined both EV fractions in HCC cell culture supernatants.…”
Section: Resultsmentioning
confidence: 99%
“…GPC-3, Glypican-3. showed that the expression of p62 and GPC-3 was significantly increased in HCC tissues compared with adjacent cirrhotic liver, and GPC-3-positive exosomes can be used for HCC detection and prediction of treatment outcomes (78). Moreover, data from the study by Montalbano reveal new aspects of the role of GPC-3 in early hepatocyte transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Glypican-3 (GPC3), a cell membrane-anchored oncofetal proteoglycan, is a novel marker of primary hepatocellular carcinoma (HCC) that outperforms the clinically commonly used alpha-fetoprotein (AFP) and performs satisfactorily in the early clinical screening of HCC [1]. However, the current methods for detecting GPC3 are mainly enzyme-linked immunoassay (ELISA), bioluminescence enzyme immunoassay (BLEIA), etc., but these methods have the disadvantages of low sensitivity, poor stability, and susceptibility to multiple factors [2,3]. Therefore, there is an urgent need for a new method of GPC3 detection that is fast and sensitive and easy to operate.…”
Section: Introductionmentioning
confidence: 99%